(untitled) (Quaderni di Gargnano, 2018)
This analysis of the all surviving letters of Francesco da Fiano sheds new light on da Fiano’s role as a promulgator of the humanistic movement of late fourteenth- and early fifteenth-century Rome and Naples. A chancellor in the papal curia, da Fiano was also a humanist who recognized how letter-writing could serve as a vehicle of intellectual expression. The essay reconstructs the life of da Fiano on the evidence of archival documents and surviving works. The cultural and historical importance of da Fiano is particularly apparent in the letters between him and Petrarch, Salutati and the major writers of the time. His importance is also reflected in his correspondence with several kings and nobles, some of whom were briefly his protectors and patrons. The style of the letters is consonant with the conventions of the Roman curia of the late fourteenth century, but the letters also incorporate several novelties proposed by Petrarch and Salutati.